2004
DOI: 10.1017/s1355617704104128
|View full text |Cite
|
Sign up to set email alerts
|

African American acculturation and neuropsychological test performance following traumatic brain injury

Abstract: The present study examined the influence of African American acculturation on the performance of neuropsychological tests following traumatic brain injury (TBI). Seventy one participants already enrolled in a larger-scale study assessing the impact of TBI (i.e., the South Eastern Michigan Traumatic Brain Injury Model Systems project) completed a self-report measure of African American acculturation (African American Acculturation Scale-Short Form; Landrine & Klonoff, 1995) in addition to a standardized battery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(42 citation statements)
references
References 39 publications
(53 reference statements)
3
39
0
Order By: Relevance
“…For example, applying norms developed for African Americans reduced the percentage of impairment in HIV1 African American men from 71% to 44%, which was closer to the 38% impairment rate of the study's non-Hispanic White males (Miller et al, 1997). Whether the best approach is to use racial0ethnic group norms that adjust for education, to use reading-grade-level based norms, to account for acculturation (Ardilia et al, 1989;Helms, 1997;Manly et al, 1998aManly et al, , 2002Kennepohl et al, 2004), some combination of these factors, or even some additional variable is uncertain. However, a recent study found that among elder African Americans, educational quality (as measured by reading level) was a more influential predictor of neuropsychological performance than acculturation (Manly et al, 2004).…”
Section: Neuropsychological Impairment In Minorities With Hivmentioning
confidence: 99%
“…For example, applying norms developed for African Americans reduced the percentage of impairment in HIV1 African American men from 71% to 44%, which was closer to the 38% impairment rate of the study's non-Hispanic White males (Miller et al, 1997). Whether the best approach is to use racial0ethnic group norms that adjust for education, to use reading-grade-level based norms, to account for acculturation (Ardilia et al, 1989;Helms, 1997;Manly et al, 1998aManly et al, , 2002Kennepohl et al, 2004), some combination of these factors, or even some additional variable is uncertain. However, a recent study found that among elder African Americans, educational quality (as measured by reading level) was a more influential predictor of neuropsychological performance than acculturation (Manly et al, 2004).…”
Section: Neuropsychological Impairment In Minorities With Hivmentioning
confidence: 99%
“…Some research has suggested that gender also has an impact (Jorm, Anstey, Christensen, & Rodgers, 2004), though other studies have found no difference (Gilmore, Royer, & Gruhn, 1983). Level of acculturation in an African American sample was found to affect scores on the written version (Kennepohl, Shore, & Nabors, 2004). Others have reportedly found an ethnicity effect on SDMT scores, although their results should be interpreted with caution as their sample contained a small portion of non-white participants (Uchiyama et al, 1994 years.…”
Section: Symbol Digit Modalities Test (Sdmt)mentioning
confidence: 80%
“…Third, racial and cultural biases need to be considered in evaluating the results of neuropsychological testing. While there are only a few studies that have examined racial differences in neuropsychological testing in the context of TBI (Kennepohl, Shore, Nabors, & Hanks, 2004), such biases have been broadly documented when testing different racial or ethnic groups (Baird, Ford, & Podell, 2007;Pedraza & Mungas, 2008;Wilkie et al, 2003). Fourth, ligation status of the patient needs to be considered, as it can often distort the clinical presentation, particularly in mild TBI (Larrabee, 1997(Larrabee, , 2000.…”
Section: Frequently Used Research Designs For the Assessment Of Tbimentioning
confidence: 99%